Metal Cutting Technologies : Progress and Current Trends. - Davim, J. Paulo (Advanced Mechanical Engineering, 2016)
This book covers current trends in metal cutting, including traditional processes (turning, milling, drilling, etc), non-traditional processes (EDM, USM, LAM, etc), abrasive cutting, high speed cutting, high efficiency cutting, micromanufacturing, and internet-based manufacturing. The interest in these topics increased rapidly over the last twenty years with advances in materials science, automation, control and computer technology.